2016
DOI: 10.1176/appi.ajp.2015.15040506
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Safety of Second-Generation Antipsychotics: Current Data From the Massachusetts General Hospital National Pregnancy Registry for Atypical Antipsychotics

Abstract: The results suggest that it would be unlikely for second-generation antipsychotics to raise the risk of major malformations more than 10-fold beyond that observed in the general population or among control groups using other psychotropic medications. If the estimate stabilizes around the null with ongoing data collection, findings may be reassuring for both clinicians and women trying to make risk-benefit treatment decisions about using atypical antipsychotics during pregnancy. These findings are timely given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
70
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 168 publications
(77 citation statements)
references
References 38 publications
3
70
1
2
Order By: Relevance
“…Registry studies have been small (<250 exposed women) and have yielded mixed results; one study 4 reported higher than expected rates of malformations (particularly cardiac), whereas another study 5 did not find this association. Results from epidemiologic studies have also yielded inconsistent evidence.…”
mentioning
confidence: 95%
“…Registry studies have been small (<250 exposed women) and have yielded mixed results; one study 4 reported higher than expected rates of malformations (particularly cardiac), whereas another study 5 did not find this association. Results from epidemiologic studies have also yielded inconsistent evidence.…”
mentioning
confidence: 95%
“…Weighing these options against each other, the recommendation has often been to discontinue treatment, especially during the first trimester 1. However, during the past decade more safety data have accumulated suggesting that antipsychotics are relatively safe to use in pregnancy 1, 2, 3. It has also been demonstrated that discontinuing ongoing maintenance treatment for severe mood and psychotic disorders during pregnancy carries a high risk of disease recurrence 2.…”
mentioning
confidence: 99%
“…However, during the past decade more safety data have accumulated suggesting that antipsychotics are relatively safe to use in pregnancy 1, 2, 3. It has also been demonstrated that discontinuing ongoing maintenance treatment for severe mood and psychotic disorders during pregnancy carries a high risk of disease recurrence 2. Thus, for women with substantial psychiatric morbidity and good treatment response, maintained use of an antipsychotic during pregnancy might often represent the best risk–benefit option.…”
mentioning
confidence: 99%
“…Discussions about the use of medications in pregnancy should include the risks of treatment and of not receiving treatment. While available safety data should be taken into consideration (1921), knowledge about which medications have been effective for the patient in the past is extremely helpful in clinical decision-making. In women with bipolar disorder, prophylaxis with lithium during pregnancy is recommended due to established efficacy, though with known maternal and infant risks (22).…”
mentioning
confidence: 99%
“…In women with bipolar disorder, prophylaxis with lithium during pregnancy is recommended due to established efficacy, though with known maternal and infant risks (22). If using antipsychotics, data suggests that neither first or second generation antipsychotics are considered major teratogens (19, 21) though second generation agents may have greater efficacy and fewer short term side effects in the treatment of bipolar disorder (23). Women who require antipsychotic medications are at higher risk for adverse maternal and perinatal outcomes compared to the general population and should be monitored (24).…”
mentioning
confidence: 99%